Kesulitan Guru IPA Kelas VIII se-Kecamatan Langkapura dalam Merencanakan dan Melaksanakan Asesmen - Kinasih Cahyono; Rini Rita T Marpaung; Berti Yolida (Universitas Lampung, 2017)
This study aims to identify the difficulties of science teachers of eighth grade at Langkapura Bandar Lampung in the academic year of 2016/2017. The difficulties include the planing and implementations of assessment for their students. Thus, all science teachers of grade VIII were selected by non probability sampling technique. This research design was descriptive. Qualitative data were obtained from the questionnaire and interviews that were analysis descriptively. The research result showed that the difficulties of science teachers in planning the assessment were classified as quite difficult to determine the purpose of the assessment, arranging the instrument, composing the lattice works of question, writing questions based on the lattice and the rules of writing questions, determining the quality criteria of question, and arranging the scoring guidelines. The difficulties in implementing the assessments were indicators of affective, psychomotor, and cognitive which was classified in high criteria. So, teachers difficulties in planning the assessment is classified in quite criteria, meanwhile implementing the assessment was high criteria.Penelitian ini bertujuan untuk mengidentifikasi kesulitan guru IPA kelas VIII SMP se-Kecamatan Langkapura Kotamadya Bandar Lampung tahun ajaran 2017/2017. Sampel penelitian ini adalah seluruh guru IPA kelas VIII yang dipilih dengan teknik sampling non probability. Desain penelitian adalah desain deskriptif. Data kualitatif diperoleh dari hasil angket dan wawancara pada guru yang dianalisis secara deskriptif. Hasil penelitian ini menunjukkan kesulitan guru IPA dalam merencanakan asesmen tergolong kriteria cukup pada indikator menetapkan tujuan asesmen, menyusun instrumen, menyusun kisi-kisi soal, menulis soal berdasarkan kisi-kisi dan kaidah penulisan soal, menentukan kriteria mutu soal, serta menyusun pedoman penskoran. Kesulitan dalam melaksanakan asesmen pada indikator pelaksanaan asesmen ranah afektif, psikomotorik, dan kognitif tergolong kriteria tinggi. Jadi, kesulitan guru dalam merencanakan asesmen termasuk kriteria cukup dan melaksanakan asesmen termasuk dalam kriteria tinggi.Kata kunci: asesmen, kesulitan, melaksanakan asesmen, merencanakan asesmen